Social Educator’s Attitude to Team Activity in School - Čiužas, Renaldas; Monkevičius, Justinas (Pedagogika, 2014)
Social educators, by providing social and educational assistance to students and by organizing social education in schools, achieves the best results by working in teams of specialists with appropriate communication and collaboration skills and able to respond flexibly to the changing needs of learners and the specific situation. Social educators in schools usually play role of the initiator of team building. Purpose of this article is to reveal the attitudes of the social educator’s to team activity in school. The method of scientific literature analysis was used. This paper describes research data, which were collected through written survey method. In order to reveal the attitudes to team activity in school of social educator’s a structured questionnaire was developed. The questionnaire consisted of 22 items, demonstrating social educators’ attitudes to teamwork in schools, 11 statements that reveal the school principals’ behavior and attitude towards teamwork in school, 11 statements that reveal the social capacity of educators to work in a team and a block of statements to gather contextual information. Likert scale was used in assessment of statements. The study involved 248 Lithuanian general education school social educators. With each respondent were contacted via email and asked to participate in the study. The questionnaires were sent to the respondents and receive from them by e-mail. The study was conducted in school year 2011/2012. All 248 completed questionnaires have been used by the data analysis. The survey results revealed that: Socio-educational assistance to students in schools or the social process of social educational in schools usually involves teams. Social educator usually plays the team builder’s initiator’s role in schools. Social educators are satisfied with their daily activities. Thy and their opinion are appreciated in school. On the view of social educators, school community is open to teamwork: community discusses and speaks about the problems; the school staff is ready to help and assist their colleagues. School leaders supports team activities in schools; promote the creativity of school community, gives freedom to act. Social educators consider the importance of their personal planning, the proper functioning in unexpected situations and problem-solving skills that are necessary regardless of whether the work is individuall or teamwork. Social educators consider also the importance of ability to help others, to discuss argumentatively, to engage others to common activities, to coordinate the group (a few people) activities. These abilities are very important and necessary for teamwork in school. School educators would like to improve conflict situations solutions skills, engaging others to common activities skills, and proper functioning in unexpected situations skills, that are very important for teamwork.